2008
DOI: 10.1007/s00431-008-0673-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased heme oxygenase-1 expression in premature infants with respiratory distress syndrome

Abstract: Oxidative stress is known to play an important role in the pathogenesis of certain severe illnesses in preterm infants. The enzyme heme oxygenase-1 (HO-1) participates in cytoprotection against oxygen radical injury. We have previously described the role of HO-1 in physiologic adaptation by demonstrating the induction of HO-1 in healthy mature neonates and asymptomatic preterm infants. Our current aim was to investigate the HO-1 expression in preterm infants with respiratory distress syndrome (RDS). We collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The increase in oxidative stress that we observed following neonatal hyperoxia in mice is consistent with findings in humans. It has been shown that preterm infants who suffered from respiratory distress and required supplemental oxygen exhibited an eightfold increase in HO-1 expression within the blood 1-5 days after birth compared with term controls (25). Furthermore, this increase in oxidative stress persists; adolescent children born very preterm had greater expression of an oxidative stress marker (8-isoprostane) in exhaled breath condensate than term-matched controls, regardless of whether they developed BPD or not (27).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The increase in oxidative stress that we observed following neonatal hyperoxia in mice is consistent with findings in humans. It has been shown that preterm infants who suffered from respiratory distress and required supplemental oxygen exhibited an eightfold increase in HO-1 expression within the blood 1-5 days after birth compared with term controls (25). Furthermore, this increase in oxidative stress persists; adolescent children born very preterm had greater expression of an oxidative stress marker (8-isoprostane) in exhaled breath condensate than term-matched controls, regardless of whether they developed BPD or not (27).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…The measurement of oxidative biomarkers was performed in different timepoints (within 12 h after birth in our study versus 14 h to 21 d in various studies 20,38,41,42 ), which may also account for the different results as the levels of these markers may increase or decrease over time. 20 Ahola et al 43 showed that erythrocyte-glutathione concentration decreased during the first week of life whereas erythrocyte-cysteine concentration increased significantly from day 3 to day 7 in preterm infants with a birthweight of 500-1500 g. Farkas et al 16 found an eight-fold increase in haeme oxygenase-1 gene expression in the preterm infants with RDS on the fifth day as compared with the first day after birth. May et al 42 showed that end tidal carbon monoxide levels on day 14, but not on day 3, significantly predicted BPD development.…”
Section: Rdsmentioning
confidence: 99%
“…Indeed, increased expression of HO-1 protein has been found in the lungs of patients with acute respiratory distress syndrome (3), in monocytes of patients with systemic inflammatory response syndrome (4), and in the bone marrow macrophages of patients dying from severe sepsis or septic shock (5). In addition, HO-1 mRNA expression is increased in the blood cells of premature infants with respiratory distress syndrome and pediatric cancer patients with systemic inflammatory response syndrome (6,7). Upregulated HO-1 mRNA and protein levels have also been found in the livers of acute liver failure patients (8).…”
Section: Introductionmentioning
confidence: 97%